1983
DOI: 10.1136/gut.24.6.532
|View full text |Cite
|
Sign up to set email alerts
|

HLA-DR phenotypes in Spanish coeliac children: their contribution to the understanding of the genetics of the disease.

Abstract: SUMMARY The DR-locus controlled B-cell antigens were studied in 163 unrelated Spanish coeliac children and 68 families of this group, nine of them with more than one coeliac patient, to obtain more information about the association between these antigens and coeliac disease. The results show that the most common coeliac phenotypes are DR3/DR7, DR7/DR5, DR3/other DR, and DR3/DR3. The family study confirmed

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
78
2
4

Year Published

1988
1988
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 168 publications
(97 citation statements)
references
References 15 publications
13
78
2
4
Order By: Relevance
“…Similar risks were observed in other populations, although these studies were conducted in an ordinary case-control setting, in which haplotypes had to be estimated. [12][13][14] Recently, a family-based study using phase-known haplotypes also demonstrated increased risk for these two genotypes. 11 A possible explanation for the increased risk may reside in the number of DQ molecules capable of gluten presentation that arise from each genotype.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar risks were observed in other populations, although these studies were conducted in an ordinary case-control setting, in which haplotypes had to be estimated. [12][13][14] Recently, a family-based study using phase-known haplotypes also demonstrated increased risk for these two genotypes. 11 A possible explanation for the increased risk may reside in the number of DQ molecules capable of gluten presentation that arise from each genotype.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, the homozygous DQA1*05-DQB1*02/DQA1*05-DQB1*02 (DR3/3) and the heterozygous DQA1*05-DQB1*02/DQA1*0201-DQB1*02 (DR3/7) genotypes were shown to be associated with increased risk. [11][12][13][14] The extended HLA-DR3-DQ2 haplotype includes many other genes that play a role in the immune response and it cannot be excluded that another HLA gene also confers increased risk to coeliac disease. The HLA region is known to display extensive linkage disequilibrium (LD).…”
Section: Introductionmentioning
confidence: 99%
“…43 In siblings sharing identical HLA haplotypes, the CD pair-wise concordance is around 20-30%, suggesting importance of genes located outside HLA in disease susceptibility. 43,58,59 With current estimates of population prevalence (0.5 -1%) the relative risk has decreased, and ls is approximately 10 -20, ls (HLA) is around 5 and thus with a multiplicative model, 60 the non-HLA component ls (non-HLA) is 2 -4 and would confer a minor part of the total genetic component. However, these measurements should be taken with caution also considering that HLA is a necessary factor.…”
Section: Epidemiology Population Geneticsmentioning
confidence: 99%
“…The 12th tube of the reaction identifies the DQB1*02 allele in homozygous, which is an important information, because studies reveal that homozygous haplotype, increases patient´s susceptibility to develop CD (17,21,22) .…”
Section: Determination Of Hla Dq2 and Dq8mentioning
confidence: 99%
“…However, trans-positioned alleles, i.e., positioned in homologous chromosome, may also codify DQ2 heterodimer. This is the case of haplotypes DRB1*07-DQA1*0201-DQB1*0202 (DR7-DQ2) and DRB1*11-DQA1*0505-DQB1*03 (DR11-DQ2) (21,25,35) . DQ8 heterodimers are codified by alleles DQA1*0301 and DQB1*0302 and due to bonding unbalance, are transmitted together with allele DRB1*04, forming the haplotype known as DR4-DQ8 (17,36,38) .…”
Section: Introductionmentioning
confidence: 99%